Calibration of the Heat Flow and Physical Properties Package (HP 3) for the InSight Mars Mission. Issue 12 (28th December 2019) - Grott, M.; Spohn, T.; Knollenberg, J.; Krause, C.; Scharringhausen, M.; Wippermann, T.; Smrekar, S.E.; Hudson, T.L.; Banerdt, W.B.
Abstract: The (HP 3 ) of the InSight Mars mission is an instrument package to measure the Martian geothermal heat flow. The instrument's platinum resistance temperature sensors have been calibrated between − 75 and + 55 °C, and the absolute temperature uncertainty of the calibration is 10 mK. Temperature differences can be measured with an uncertainty of better than 5 mK. HP 3 determines regolith thermal conductivity by using the HP 3 mole as a modified line heat source, and thermal conductivity can be measured with an uncertainty of better than 4%. Tilt sensors used to determine the attitude of the mole during penetration measure tilt with an uncertainty of better than 0.25°. Key Points: The Heat Flow and Physical Properties Package (HP 3 ) of the InSight Mars mission is a heat flow probe designed to measure the temperature gradient and thermal conductivity of the Martian regolith to a depth of 5 m To reconstruct sensor depth, tiltmeters measure the emplacement angle with an uncertainty of better than 0.25° Temperature sensors have been calibrated to measure temperature difference with an uncertainty of better than 5 mK; thermal conductivity can be measured with an uncertainty of better than 4%; all stated uncertainties are 1 σ confidence limits